EFEKTIVITAS PEPAYA (Carica Papaya L) TERHADAP KELANCARAN PRODUKSI ASI PADA IBU MENYUSUI - Ifni Wilda; Nelfi Sarlis (LPPM Universitas Abdurrab, 2021)
Breast milk is breast milk that contains optimal nutrition, both in quantity and quality, however, in fact, the coverage of breast milk in Indonesia is not in accordance with the expected target, namely 80%, like in 2011 the coverage of breast milk in Indonesia was 61.50%. Young papaya is a natural plant acts as a lactogum because it can increase and facilitate the production of breast milk. The purpose of this research is to determine the effectiveness of young papaya (carica papaya L) on the smooth production of mother's milk breastfeeding. This type of research used quantitative with quasi experiments. This research conducted in The working area of ​​Puskesmas Sentajo Raya Teluk Kuantan in 2020. The population in this study were all mothers 81 breastfeeding children under 6 months of age who are in the Work Area Sentajo Raya Puskesmas and a sample of 15 people. The sampling technique used consecutive sampling. Univariate and bivariate data analysis Bivariate analysis was performed using thetest Wilcoxon. Research result It was found that the effectiveness of young papaya on the smooth production of breast milk, with a p value <α, namely 0.001 <(0.05). It is recommended to health workers at the Sentajo Raya puskesmas to increase knowledge regarding non-pharmacological therapy in increasing breast milk production, especially the effectiveness of young papaya against smoothness of breast milk in nursing mothers.